2023
DOI: 10.1177/08850666231183396
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Adrenal Insufficiency

Abstract: In sepsis, dysregulation of the hypothalamic–pituitary–adrenal axis, alterations in cortisol metabolism, and tissue resistance to glucocorticoids can all result in relative adrenal insufficiency or critical illness-related corticosteroid insufficiency (CIRCI). The symptoms and signs of CIRCI during sepsis are nonspecific, generally including decreased mental status, unexplained fever, or hypotension refractory to fluids, and the requirement of vasopressor therapy to maintain adequate blood pressure. While we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It has also been reported that cortisol values are higher in patients with lung insufficiency and sepsis than in those with gastrointestinal bleeding. 7 Furthermore, diseases that prompt rapid admission to the ICU may lead to high cortisol values, which could independently predict patient outcomes. 8 - 10 De Castro et al 8 shown that basal cortisol levels, measured upon admission of patients with septic shock and severe sepsis to the ICU, are the best prognostic factor for 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that cortisol values are higher in patients with lung insufficiency and sepsis than in those with gastrointestinal bleeding. 7 Furthermore, diseases that prompt rapid admission to the ICU may lead to high cortisol values, which could independently predict patient outcomes. 8 - 10 De Castro et al 8 shown that basal cortisol levels, measured upon admission of patients with septic shock and severe sepsis to the ICU, are the best prognostic factor for 28-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Growing concerns among intensivists are centered around critical-illness-related corticosteroid and mineralocorticoid deficiencies ( 3 , 4 ). The International Guideline of Surviving Sepsis Campaign conditionally recommended administration of IV hydrocortisone at a typical dose of 200 mg/d to adult patients with septic shock necessitating vasopressor support ( 5 ).…”
mentioning
confidence: 99%